Pengaruh Total Asset Turnover (Tato) dan Debt Ratio (Dr) terhadap Profitabilitas pada Perusahaan Sektor Makanan dan Minuman yang Terdaftar di BEI Periode Tahun 2015-2018 - Sari, Dian Novita; Hermawan, Sigit (Innovative Technologica: Methodical Research Journal, 2023)
This study aims to determine the effect of total asset turnover (TATO) and debt ratio (DR) on profitability in food and beverage companies listed on the Indonesia Stock Exchange for the 2015-2018 period. This type of research is quantitative with purposive sampling technique. This study uses 10 food and beverage companies listed on the Indonesia Stock Exchange in the 2015-2018 period. The data sources for this research are annual reports, financial statement data, and market data by sample companies. The analytical tool used is data tabulation, data collection in the form of normality test, t test, F test, and determinant test. The results showed that TATO and DR simultaneously had a significant positive effect on ROA. Partially, TATO does not have a significant effect on ROA, DR has a significant negative effect on ROA.